PIC18F452 Microcontroller Home Security System: A Review Paper (International Journal of Innovative Research in Computer Science & Technology, 2022)
For we picked a PIC18F452 microchip for  the design and simulation of their home automation designs.  Built also on PIC18F452, our sensor measures a home's  glass doors and transmit an alert and then a warmer signals  to a local or regional scale. Call the police if someone  attempts to destroy in. This safeguard has been  implemented. It may also recognize the landlord's  identification card. Gain entrance to the house without  disarming the alarm system or setting off the alarm. The  access control also assigns a – anti independence. Keep a  watch on the bedroom doors and there's a potential of a  break-in. The system is continually verifying the state of  their house, which the landlady does not want. As a way of  avoiding burglary as well as theft, the installation of a  security system has gained in popularity. Embedded linux  can now bring stability by observing people's houses thanks  to substantial developments in microcontroller units. We  designed a surveillance system using a PIC18F452  computer that can monitoring a landlord's windows. The  idea is to design a home alarm system that utilizes series of  linear switches doors.
Keywords: Arrays; Embedded Systems; Light Emitting Diodes; Microcontrollers; Monitoring Hardware